To Teach Or Not To Teach: Sex Education In Islamic Boarding School - Sriyanti, Lilik; Erawati, Muna; Prabawa, Abi Fa'izzarahman; Antika, Eni Rindi; Jati, Roko Patria (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Homosexuality is a significant topic in many social discussions. Most people believe in the right for individuals to live as they are and appreciate everyone's uniqueness. However, there are also those with differing opinions who do not support this right. Islamic boarding school serves as one of the pillars of preserving Islamic teachings and protecting the young generation from moral decadence. Ironically, it is often viewed as one of the places where sexual perversion, i.e., homosexuality, grows. This study aimed to present a preventive intervention to prevent sexual perversion through capacity building for the management, head, and teachers in the Islamic boarding school environment. To this end, the action research was conducted in one of the Islamic seminaries in Magelang Regency, Indonesia. The study subjects were the Islamic boarding school's manager, caretakers, and teachers. Data were collected through questionnaires, in-depth interviews, observation, focus group discussion (FGD),  and document study. This study found that (1) the indication of homosexual perversion in the Islamic boarding school was categorized as low; (2) the intervention could improve managers’, caretakers’, and teachers’ knowledge about the indication of homosexual perversion, reproductive education strategies for students, and sensitivity towards homosexual perversion in the Islamic boarding school; and (3) it is necessary to reconstruct the regulation and prepare counseling service units. To prevent homosexuality at Islamic boarding schools (IBS), there's a need for a systematic, integrated, comprehensive, and wise preventive effort involving managers, caretakers, and teachers. This includes increasing their knowledge and awareness about various topics such as: 1) Sexual behavior issues at IBS and their underlying causes; 2) Adolescents' development characteristics; 3) Adolescent reproductive health; 4) Sexually transmitted diseases and their causes; 5) Sexual deviations and their consequences; 6) Future planning. Additionally, efforts should involve reconstructing IBS regulations and preparing counseling service units. The suggestion from this research is to adapt these interventions to similar educational institutions in a thoughtful manner.